BOOK REVIEW: LIDIA RAQUEL MIRANDA (ED.). METAPHOR AND EPISTEME: TOWARDS A HERMENEUTICS OF INSTITUTIONS. NEUQUÉN: HERMENEUTIC CIRCLE, 2017. ISBN: 978-987-45956-7-6. 282 PAGES (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
BOOK REVIEW: LIDIA RAQUEL MIRANDA (ED.). METAPHOR AND EPISTEME: TOWARDS A HERMENEUTICS OF INSTITUTIONS. NEUQUÉN: HERMENEUTIC CIRCLE, 2017. ISBN: 978-987-45956-7-6. 282 PAGES
Keywords: metaphor; episteme; institutions; review